2012
DOI: 10.1007/s00411-012-0411-3
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-ray thermoluminescence measurements: a record of fallout deposition in Hiroshima?

Abstract: In certain Hiroshima neighborhoods, radiation measurements using thermoluminescence dosimetry (TLD) exceed what can be explained by the initial gamma-ray doses and uncertainties from the Dosimetry System 2002 (DS02). This problem was not previously recognized as being isolated to certain parts of that city. The ratio between TLD measurements and DS02 dose calculations for gamma rays appear to grow larger than unity up to more than three with increasing ground range, but closer examination shows the excess TLD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Egbert) Measurements of thermoluminescence (TL) of tiles in several areas in Hiroshima indicated measured doses larger by up to 0.8 Gy than could be explained by exposure to initial radiation from the detonation. This excess dose was particularly noticeable in four areas around the city (Egbert and Kerr 2012). It was suggested that this was due to some sources of radiation that are unique to the Hiroshima detonation.…”
Section: Radiation Dosimetry Study In Hiroshima (M Hoshi)mentioning
confidence: 98%
See 4 more Smart Citations
“…Egbert) Measurements of thermoluminescence (TL) of tiles in several areas in Hiroshima indicated measured doses larger by up to 0.8 Gy than could be explained by exposure to initial radiation from the detonation. This excess dose was particularly noticeable in four areas around the city (Egbert and Kerr 2012). It was suggested that this was due to some sources of radiation that are unique to the Hiroshima detonation.…”
Section: Radiation Dosimetry Study In Hiroshima (M Hoshi)mentioning
confidence: 98%
“…Thus, the most likely source of a significant residual radiation exposure to survivors near the hypocenter areas at Hiroshima and Nagasaki appears to result from (1) the lofting of neutron-activated radionuclides from soil and other environmental materials into the atmosphere by the ground shock from the blast wave of the explosion (see Figs. 1 and 2) and (2) the horizontal scouring and sweeping of ground and river water by the blast wave, which moved some neutron-activated materials to larger ground distances (Egbert and Kerr 2012).…”
Section: Workhop On Residual Radiation Exposures At Hiroshima and Namentioning
confidence: 99%
See 3 more Smart Citations